INVESTIGATION OF NUMERICAL ANALYSIS IN THE EFFECT OF COMPARISON OF INLET AND OUTLET DIAMETER OF GUIDE VANE ON VELOCITY PROFILE - Roy Ama Ratu; Fajar Anggara (Scientific Journal of Mechanical Engineering Kinematika, 2020)
Because of the very uneven or spread wind output of condenser, it is necessary to design ducting as the condenser wind flow directors. It is expected to be able to direct the condenser wind output flow and maintain the stability of the amount of wind that will be received by the propeller. One of the ways is by making variations in the design of the ducting and guide vane ducting in order to get the optimal flow or wind gusts from the flow of wind that will be exhaled by the condenser. The aim of this research is to find the effect of dimension ratios and the best ratio value to the variation of profile ducting design using a comparison of the dimensions of the guide vane diameters and the length of the guide vane with the Computational Fluid Dynamics (CFD) method. In this research using the ratio of the guide vane diameter that is contained D1 and D2 on the guide vane diameter. With the results of the investigation produce the best and optimal design to flow condenser wind flow where Variation C provides a maximum speed of 7m / s to 7.2 m / s and directs to moving and rotating blades or blades generator.